Zen conquests: Buddhist transformations in contemporary Vietnam - Soucy, Alexander Duncan (University of Hawaiʻi Press, 2022)
The Rise of Zen in Twentieth Century Vietnam -- The Sùng Phúc Zen Monastery -- Secular Buddhism -- Nationalism and Internationalism -- Zen Women -- Zen Men -- Zen for All Ages.